Old, new, borrowed and blue – shifts in modern policing - Dahl, Johanne Yttri (The British journal of criminology, 2022)
This article analyses ambiguity and complexity in proactive policing practices and identifies the paradox that despite the focus on increasing proactivity, police work remains strongly reactive. Drawing on a set of Norwegian case studies of policing in different domains, the article shows how under an overarching objective of ‘combating crime’, the distinctions between non-coercive (mainly proactive) forms of prevention or (mainly reactive) methods such as investigation or intelligence are seen as unimportant. This creates a demand for professionals working across different crime types, leading to a shift towards high policing in everyday life and tension between experts and generalists. Other, unintended consequences include a fragmentation of tasks and a more general and abstract way of policing. The result is pluralization and multiagency partnership strategies, where the police conduct high-policing tasks and external actors conduct low-policing tasks. These findings point to the emergence of new forms of hybrid of policing.